Could probiotics be used as a novel therapeutic approach to alleviate the reproductive and neurobehavioral side effects of sertraline? A study in male mice - Lozano, Ana Flávia Quiarato [UNESP]; Guimarães, Isabella Cena [UNESP]; González, Lucas Nicolás; Cuasnicu, Patricia Sara; Cohen, Débora Juana; De Grava Kempinas, Wilma [UNESP] (Elsevier, 2025)
There are still few studies that have investigated the impact of sertraline (SE) on fertility, as well as adjuvant treatments that alleviate its side effects. Thus, the present study aimed to investigate the impact of SE on reproductive and neurobehavior parameters and verify whether the probiotic Lactobacillus rhamnosus alleviates the side effects of SE. After carrying out a dose-response study with SE, experiment II was conducted. Thus, male mice were distributed into four experimental groups (n=8–9/group): control (CO)-received filtered water (vehicle); sertraline group (S)–received 20 mg/kg of SE, diluted in the vehicle; probiotic (P)-received the probiotic Lactobacillus rhamnosus (1×109 CFU) diluted in the vehicle; and SP group that received both probiotic and SE. The treatment occurred/lasted for 30 days. At the end of treatment, behavioral aspects were analyzed. After euthanasia, the organs were weighed, the histology of the testis and epididymis were analyzed, and the sperm quality and also natural fertility were verified. Complementarily, in vitro assays were carried out to verify whether sertraline could affect sperm capacitation and embryonic development. The results showed that the SP group, compared to S, did not reduce body weight and seminal gland weight and presented a lower number of resorptions. Notably, the rate of resorption in both the SP and S groups was similar to that of the control group. It was also observed that the S group was less exploratory and more anxious than the SP group. Thus, the present study demonstrated that SE has an impact on the reproductive system and neurobehavior. Therefore, for the first time, we demonstrate that the probiotic can alleviate the side effects of SE.
Keywords: Mice; Neurobehavior; Probiotic; Reproductive system; Sertraline